2018
DOI: 10.1007/s10803-018-3494-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Obesity in Children with Autism Spectrum Disorder Among Primary Care Pediatricians

Abstract: Children with autism spectrum disorder (ASD) are at high risk for being overweight and obese. Little is known about how obesity in children with ASD is being addressed in primary care. This article reports findings from a survey completed by 327 general pediatricians, which included a fictional clinical vignette and Likert-scales assessing attitudes, practices, self-efficacy, and barriers to obesity management. Although the majority of respondents agreed pediatricians should be the main providers to manage obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
(54 reference statements)
0
7
0
2
Order By: Relevance
“…18,19 In addition, a relationship has been observed between pharmacological therapies, disordered sleep and weight gain in individuals with the disorder. 20 In individuals with ASD, being overweight and obese, in addition to constituting a risk factor for cardiovascular disorders, may contribute to the worsening of social isolation, due to the individual and also society's lack of acceptance of their body image. 21 It is worth noting that the present study also points to an expressive consumption of ultra-processed foods, which the healthy eating guide advises against for the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In addition, a relationship has been observed between pharmacological therapies, disordered sleep and weight gain in individuals with the disorder. 20 In individuals with ASD, being overweight and obese, in addition to constituting a risk factor for cardiovascular disorders, may contribute to the worsening of social isolation, due to the individual and also society's lack of acceptance of their body image. 21 It is worth noting that the present study also points to an expressive consumption of ultra-processed foods, which the healthy eating guide advises against for the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…The extant research on weight management, body weight, and body image among autistic adults is incomplete. These topics are, however, increasingly studied in children with ASD, their parents, and health care providers (Jachyra et al, 2018;Mcpherson et al, 2021;Walls et al, 2018). Findings from these studies provide critical information on how health services and supports might be best tailored to meet the needs of children with ASD.…”
mentioning
confidence: 99%
“…Research has identified many barriers to HCPs discussing weight with typically developing children and their families, including a lack of training, confidence, time, and resources [46,47]. ASD adds an additional layer that makes this even more challenging [48], especially when parents are overwhelmed with managing their child's health and behaviour [11]. Furthermore, previous research has shown that HCPs who prescribe antipsychotic medication to children with ASD to manage upsetting behaviours (e.g., self-harm, violence towards others) experience some moral distress when the medication causes rapid weight gain and they lack the expertise to address it [11].…”
Section: Discussionmentioning
confidence: 99%